The Coca-Cola Pavilion (Plastichrome of Texas, Inc.)
Coke presents the world-renewed puppets of Sid and Marty Krofft in a new mixed-media show, "Kaleidoscope". Adults as well as children are delighted by the puppets, ranging from tiny dancing banjos to massive movie stars.